INDICES OF FECUNDITY IN THE HILLSTREAM FISH GARRA MULLYA - Somvanshi, V S (Indian Journal of Fisheries, 2011)
The fecundity of Garra miillya in relation to fish length, fish weight, gonad length and gonad weight are worked out and equations using regression and multiple regression analyses are given. The equation on the gonad lengthfecundity relationship gives more reliable fecundity estimate. The fecundity is discussed as a manifestation of aging and as an adaptation to the ecological conditions peculiar to the hillstreams, terming this adaptation, together with the morphological adaptations of the fish, as "bioecological adaptation."